The Forfeiture of Corruption Assets and the Legal Position of Innocent Third Parties: Normative Challenges and Policy Gaps - Syauqi Huda, Kholilah Delvi; Yuliati, Yuliati; Sugiri, Bambang (Institut Agama Islam Negeri Ponorogo, 2025)
The asset forfeiture of corruption proceeds is essential for recovering state losses and preventing criminals from benefiting economically from their crimes. However, this policy raises legal challenges when assets are in the hands of third parties acting in good faith. This study aims to explore the economic rights of such third parties and examine the legal protection of their rights during the seizure of assets derived from corruption. This study employs a normative juridical approach, utilizing statutory, conceptual, and case analyses. The findings reveal an imbalance between asset forfeiture policies and the principle of justice for third parties who acquire assets legally. Although regulations govern objections from good-faith third parties, practical implementation still faces difficulties in terms of proof and legal interpretation. Thus, this study suggests the need for more detailed regulatory reforms to ensure the fair protection of the economic rights of good-faith third parties while facilitating the recovery of state assets.